A metal-free approach to highly functionalized 3-substituted-3-arylbenzofuran-2(3H)-ones. (7th November 2022) - Dhotare, Bhaskar B.; Kumar, Sahil; Wadawale, Amey; Nayak, Sandip K.; Kumar, Mukesh; Goswami, Dibakar
Abstract : A novel approach for H2 SO4 -mediated dehydrative substitution of 3-hydroxy-3-phenylbenzofuran-2(3 H )-ones with electron-rich arenes/1, 3-diones/alcohols/thiols as nucleophiles is presented. Abstract : A novel metal-free approach to the synthesis of a variety of 3-substituted-3-arylbenzofuran-2(3 H )-ones is developed via H2 SO4 -mediated dehydrative substitution of 3-hydroxy-3-phenylbenzofuran-2(3 H )-ones with electron-rich arenes/1, 3-diones/alcohols/thiols as nucleophiles in moderate to good yields. Mechanistically, the substitution with the alkoxy group proceeds via a phenolic–hydroxyester intermediate, and forms the desired product via cascade dehydration–relactonization steps.